Computational Statistics with Spreadsheets Towards Efficiency, Reproducibility and Security - Gökhan Aydınlı; Wolfgang Karl Härdle; E. Neuwirth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
The use of electronic spreadsheets as the primary software tool for teaching management science modeling techniques and quantitative methods in economics and finance undoubtedly played a key role in the increasing impact of quantitative lectures given in graduate programs. Researchers suggest that the ability to extract data from various sources and embed analytical decision models within larger systems are two of the most valuable skills for business students entering today?s IT dominated workplace. In this paper we will try to contribute to this evolution and furthermore want to argue in favor of spreadsheet applications as appropriate interface solution to matrix oriented statistical languages. We present two software solutions which are aimed to combine statistical method servers and the spreadsheet application Excel. We will emphasize the productivity gain in terms of transparency and reproducibility available by combining the computational power of a statistical programming environment with the direct manipulation facilities available in spreadsheet programs like Excel. We also want to stimulate the discussion of securing the communication in such a client/server environment.
urn:nbn:de:kobv:11-10050260
Keywords: 330; Statistics in education and practice; Spreadsheets; Client / Server based statistical Computing; Security; XploRe; R; Statistische Methodenlehre; PC-Software; XploRe